Assessment of Genetic Diversity at the Heamoglobin Locus in Selected West African Dwarf Goat Populations in Nigeria - D.S, Gwaza; H.O, Ukwu; J.M, Iorungwa (The International Journal of Biotechnology, 2019)
Blood samples were collected from 40 (forty) goats in Kwande Local Government Area, of Benue State, Nigeria. Blood samples collected were subjected to electrophoresis to study haemoglobin polymorphism and its distribution in West African Dwarf goat populations in Kwande. Data on Haemoglobin genotypes were subjected to sample variance (S2) population genetics simulation software for the analysis. Three heamoglobin genotypes (HbAA, HbAB and HbBB) were observed in the West African dwarf goat populations. The haemoglobin gynotypes (HbAA, HbAB and HbBB) were controlled by two co-dominant haemoglobin alleles HbA and HbB. The genotypic frequencies were 0.24, 0.57 and 0.19 for HbAA, HbAB and HbBB respectively. Genotypic frequencies at the haemoglobin locus in West African Dwarf goat were in hardy-weinberg equilibrium. The gene frequencies of HbA and HbB observed were 0.52 and 0.48 respectively with HbA being the most frequent. The low allelic variation may have occur when populations are separated but only for a short time, that the processes of genetic drift and mutation that leads to differentiations of allelic frequencies at selected loci are yet to occur. As the amount of time in which two isolated populations increases, the differences in allelic frequencies will also increase until each population is completely fixed for a number of alleles. These factors may have accounted for the low variation in the heamoglobin allelic frequencies observed in this study. There was also gene-controlled diversity at the haemoglobin locus in the WAD goat populations with heterozygosity (He) value of 0.49, which indicated a moderate level of genetic diversity at the haemoglobin locus in WAD goat populations in Kwande Local Government Area of Benue State, Nigeria.